2022
DOI: 10.3389/fonc.2022.952228
|View full text |Cite
|
Sign up to set email alerts
|

Osteosarcoma immune prognostic index can indicate the nature of indeterminate pulmonary nodules and predict the metachronous metastasis in osteosarcoma patients

Abstract: PurposeThe relationship between indeterminate pulmonary nodules (IPNs) and metastasis is difficult to determine. We expect to explore a predictive model that can assist in indicating the nature of IPNs, as well as predicting the probability of metachronous metastasis in osteosarcoma patients.Patients and methodsWe conducted a retrospective study including 184 osteosarcoma patients at West China Hospital from January 2016 to January 2021. Hematological markers and clinical features of osteosarcoma patients were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 66 publications
(59 reference statements)
0
3
0
Order By: Relevance
“…Current standard treatments for OS include neoadjuvant chemotherapy, surgical resection of the primary tumor, and adjuvant chemotherapy. However, the prognosis for metastatic or recurrent OS has not significantly improved ( He et al, 2022 ). Traditional clinical markers have limited predictive capabilities because the molecular mechanisms underlying OS are unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Current standard treatments for OS include neoadjuvant chemotherapy, surgical resection of the primary tumor, and adjuvant chemotherapy. However, the prognosis for metastatic or recurrent OS has not significantly improved ( He et al, 2022 ). Traditional clinical markers have limited predictive capabilities because the molecular mechanisms underlying OS are unclear.…”
Section: Discussionmentioning
confidence: 99%
“…He et al demonstrated creativity by developing OIPI, a predictor speci cally designed for bone tumors. They combined the role of LIPI in lung cancer to create OIPI, which plays a crucial role in predicting the prognosis and metastasis of bone tumors 20,21 . To date, there has been no reports on the prognostic effect of LIPI in patients with ICC.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, creating a prognostic model to effectively estimate the survival of individuals with ependymomas is essential. A nomogram, which is a precise and user-friendly tool, can evaluate risk factors and predict tumor prognosis (5). The Surveillance,Epidemiology,and End Results (SEER) database in the United States collects comprehensive patient information, clinicopathological characteristics, and treatment data for about a third of the U.S. population, making it a valuable resource for studying cancer outcomes.…”
Section: Introductionmentioning
confidence: 99%